Visualizing Patients’ Unreliability - Vaccarella, Maria (Status Quaestionis, 2014)
In graphic storytelling, insight into characters’ consciousness and cues to the fictive reality around them are highly condensed: as it is often the case, characters’ perception of reality (in captions or bubbles) overlaps with the surrounding reality (visually represented) in the same panel. According to Seymour Chatman’s traditional definition of unreliability in literary works, the unreliable narrator’s account diverts from the implied reader’s speculations about the story: then, how do graphic novelists manage narrative unreliability when it stems out of the narrator’s (maybe temporary) cognitive impairment, not from greed or credulity or lack of information? Furthermore, in graphic pathographies on neurological conditions, the narrator is a carer, not the patient: what is the role of narratorial intervention here and which techniques are privileged to raise ontological doubts in graphic storytelling? More importantly, how can authors represent this kind of unreliability, so that it engenders sympathy, rather than suspicion in the reader?